Resequencing of 145 Landmark Cultivars Reveals Asymmetric Sub-genome Selection and Strong Founder Genotype Effects on Wheat Breeding in China - Hao, Chenyang; Jiao, Chengzhi; Hou, Jian; Li, Tian; Liu, Hongxia; Wang, Yuquan; Zheng, Jun; Liu, Hong; Bi, Zhihong; Xu, Fengfeng; Zhao, Jing; Ma, Lin; et al. (Molecular plant, 2020)
Controlled pedigrees and the multi-decade timescale of national crop plant breeding programs offer a unique experimental context for examining how selection affects plant genomes. More than 3000 wheat cultivars have been registered, released, and documented since 1949 in China. In this study, a set of 145 elite cultivars selected from historical points of wheat breeding in China were re-sequenced. A total of 43.75 Tb of sequence data were generated with an average read depth of 17.94× for each cultivar, and more than 60.92 million SNPs and 2.54 million InDels were captured, based on the Chinese Spring RefSeq genome v1.0. Seventy years of breeder-driven selection led to dramatic changes in grain yield and related phenotypes, with distinct genomic regions and phenotypes targeted by different breeders across the decades. There are very clear instances illustrating how introduced Italian and other foreign germplasm was integrated into Chinese wheat programs and reshaped the genomic landscape of local modern cultivars. Importantly, the resequencing data also highlighted significant asymmetric breeding selection among the three sub-genomes: this was evident in both the collinear blocks for homeologous chromosomes and among sets of three homeologous genes. Accumulation of more newly assembled genes in newer cultivars implied the potential value of these genes in breeding. Conserved and extended sharing of linkage disequilibrium (LD) blocks was highlighted among pedigree-related cultivars, in which fewer haplotype differences were detected. Fixation or replacement of haplotypes from founder genotypes after generations of breeding was related to their breeding value. Based on the haplotype frequency changes in LD blocks of pedigree-related cultivars, we propose a strategy for evaluating the breeding value of any given line on the basis of the accumulation (pyramiding) of beneficial haplotypes. Collectively, our study demonstrates the influence of “founder genotypes” on the output of breeding efforts over many decades and also suggests that founder genotype perspectives are in fact more dynamic when applied in the context of modern genomics-informed breeding. Resequencing 145 landmark cultivars revealed the reshaped and optimized processes involved in changing the genomic landscape of new cultivars since the 1950s. Significant asymmetric breeding selection was detected among the three sub-genomes. A strategy was proposed for evaluating the breeding value of any given line on the basis of the accumulation of very large, beneficial haplotypes in centromere-spanning LD blocks.